SOSIALISASI ELECTRONIC-COMMERCE UNTUK MENINGKATKAN PENGETAHUAN DAN PENDAPATAN UMKM MEBEL DI BUKIR KOTA PASURUAN - Wahyuni, Hari (Fokus ABDIMAS, 2023)
Bukir Village is part of the Pasuruan City area where the majority of the population make a living as furniture craftsmen. Based on the observations we made there, the products produced by the furniture craftsmen at Bukir were quite varied, including carved shapes, minimalism, and contemporary motifs following developments in world products. The purpose of this service is to add insight regarding electronic-commerce so that they can market their products on the marketplace and increase the income of furniture MSMEs in the Bukir area, Pasuruan city. The approach method that we use is lecture, presentation and question and answer/discussion methods. The form of participation of the furniture craftsmen in the implementation of this activity was quite active and welcomed. We explained that by doing marketing through e-commerce-based digital facilities, MSME actors can save on promotion costs and capital can be used for developing their business. By placing orders online they can increase the number of sales and income, besides that transactions are made easier, more practical and safer. We also teach how to sell on the marketplace. Keywords: Electronic–commerce, Furniture, Knowledge, Income.